2020
DOI: 10.1177/1362361320981319
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating the disadvantage for autistic job seekers: An initial evaluation of adapted employment interview questions

Abstract: Despite possessing valuable skills, social communication differences mean that autistic people are frequently disadvantaged in job interviews. We examined how autistic and non-autistic adults compared on standard (unmodified) job interview questions, and then used these findings to develop and evaluate supportive adaptations to questions. Fifty adults (25 autistic, 25 non-autistic) took part in two mock job interviews. Interview 1 provided a baseline measure of performance when answering typical, unmodified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 75 publications
0
41
0
5
Order By: Relevance
“…We partly answer the calls for existing mainstream HR research to stop treating employees as an undifferentiated mass [ 63 ], and we acknowledge the importance of differentiated HR practices that capture the unique needs of diverse groups of employees [ 41 ]. This appears to be particularly important against a backdrop of calls for more theoretical and empirical research exploring the inclusion of individuals with autism into employment [ 38 , 43 ], and the majority of research efforts not focusing beyond the first stages of the employment cycle (e.g., [ 36 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We partly answer the calls for existing mainstream HR research to stop treating employees as an undifferentiated mass [ 63 ], and we acknowledge the importance of differentiated HR practices that capture the unique needs of diverse groups of employees [ 41 ]. This appears to be particularly important against a backdrop of calls for more theoretical and empirical research exploring the inclusion of individuals with autism into employment [ 38 , 43 ], and the majority of research efforts not focusing beyond the first stages of the employment cycle (e.g., [ 36 ]).…”
Section: Discussionmentioning
confidence: 99%
“…First, most existing research on ASD and employment focuses on the challenges related to the recruitment and selection processes of people with autism [ 35 , 36 ]. By exploring potential improvements in the onboarding and retention practices, we contribute to the lacuna of research addressing these subsequent stages where individuals with ASD are reported to suffer most from stress and ill mental health [ 19 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recall quality in employment interviews. Maras et al (2021) examined the efficacy of adapted employment interview questions for improving the quality of candidates' recall. A total of 25 autistic and 25 TD participants underwent mock employment interviews, in two phases approximately 6 months apart.…”
Section: Overview Of Original Studiesmentioning
confidence: 99%
“…The explicit use of support (such as using specific questions and detailed instructions) has also recently been shown to reduce inaccurate and improve accurate reporting (Almeida et al, 2019;Maras et al, 2013Maras et al, , 2020Mattison et al, 2015Mattison et al, , 2018, improve recall specificity (i.e. of specific events with rich contextual detail), and relevance (Norris et al, 2020), and improve the quality of autistic adults' responses in employment interviews (Maras et al, 2021).…”
mentioning
confidence: 99%
“…Despite an increasingly virtual and asynchronous world, the most common selection tool likely remains the face-to-face or two-way interview ( Campion et al 1997 ; Huffcutt et al 2001 ). They are so ubiquitous, in fact, that most previous hiring and autism research has focused on how to prepare the autistic candidate for the interview (e.g., Higgins et al 2008 ; Kumazaki et al 2019 ; Smith et al 2014 ; Strickland et al 2013 ) with only a recent shift to how the interview can change to be more inclusive ( Maras et al 2021 ). Growing in parallel to this literature is a growing body of evidence that, put simply, traditional interviews are poorly suited for assessing autistic candidates.…”
Section: Introductionmentioning
confidence: 99%